Bis(trans-cinnamaldehyde)-1,3-propanediimine) mercury(II)chloride, [Hg(BPPPB)Cl2] as Carrier for Construction of Iodide Selective Electrode - G. Karimipour; S. Gharaghani; R. Ahmadpour (E-Journal of Chemistry)
Highly selective poly(vinyl chloride) (PVC) membrane of iodide ion selective electrode based on the application of bis(trans-cinnamaldehyde)-1,3-propanediimine)mercury(II)chloride [Hg(BPPPB)Cl2] as new carrier by coating the membrane ingredient on the surface of graphite electrodes has been reported. The effect of various parameters including membrane composition, pH and possible interfering anions on the response properties of the electrode were examined. At optimum conditions, the proposed sensor exhibited Nernstian responses toward iodide ion in a wide concentration range of 1×10-6 to 0.1 M with slopes of 58.0±0.8 mV per decade of iodide concentration over a wide pH range of 3-11 with detection limit of detection of ~8×10-7 M. The sensors have stable responses times of ≤ 5 s and give stable response after conditioning in 0.05 M KI for 24 h with its response is stable at least 2 months without any considerable divergence in its potential response characteristics. The electrodes were successfully applied for the direct determination of iodide ion in water sample and as indicator electrodes in precipitation titrations.